Fine mapping of QPm.caas-3BS, a stable QTL for adult-plant resistance to powdery mildew in wheat (Triticum aestivum L.) - Yan Dong; Dengan Xu; Xiaowan Xu; Yan Ren; Fengmei Gao; Jie Song; Aolin Jia; Yuanfeng Hao; He Zhonghu; Xianchun Xia (Springer, 2022)
Powdery mildew is a devastating foliar disease occurring in most wheat-growing areas. Characterization and fine mapping of genes for powdery mildew resistance can benefit marker-assisted breeding. We previously identified a stable quantitative trait locus (QTL) QPm.caas-3BS for adult-plant resistance to powdery mildew in a recombinant inbred line population of Zhou8425B/Chinese Spring by phenotyping across four environments. Using 11 heterozygous recombinants and high-density molecular markers, QPm.caas-3BS was delimited in a physical interval of approximately 3.91 Mb. Based on re-sequenced data and expression profiles, three genes TraesCS3B02G014800, TraesCS3B02G016800 and TraesCS3B02G019900 were associated with the powdery mildew resistance locus. Three gene-specific kompetitive allele-specific PCR (KASP) markers were developed from these genes and validated in the Zhou8425B derivatives and Zhou8425B/Chinese Spring population in which the resistance gene was mapped to a 0.3 cM interval flanked by KASP14800 and snp_50465, corresponding to a 431 kb region at the distal end of chromosome 3BS. Within the interval, TraesCS3B02G014800 was the most likely candidate gene for QPm.caas-3BS, but TraesCS3B02G016300 and TraesCS3B02G016400 were less likely candidates based on gene annotations and sequence variation between the parents. These results not only offer high-throughput KASP markers for improvement of powdery mildew resistance but also pave the way to map-based cloning of the resistance gene.